Three-dimensional computed tomographic angiography in the diagnosis and conservative management of cesarean scar pregnancy with prominent neovascularization - Akihiro Takeda; Sanae Imoto; Kotaro Sakai; Hiromi Nakamura (Elsevier, 2014)
Objective: Cesarean scar pregnancy (CSP) is a rare potentially life-threatening form of ectopic gestation. However, optimal management has not yet been established. Furthermore, there are limited reports on the diagnostic value of three-dimensional computed tomographic angiography (3D-CTA) for the conservative management of this disorder. Case report: A 33-year-old woman (gravida 3, para 2), with two previous deliveries by low segmental transverse cesarean section, was referred after 5 weeks of amenorrhea. Her serum beta-human chorionic gonadotropin (β-hCG) value was 2921 mIU/mL. Cesarean scar pregnancy was diagnosed by ultrasonography and magnetic resonance imaging. On 3D-CTA, a prominent uteroplacental neovascularized mass was identified. It was supplied by the left uterine artery and a thick draining left ovarian vein. After three cycles of systemic methotrexate (MTX) administration, the serum β-hCG value decreased to 142 mIU/mL. However, the gestational sac enlarged and peritrophoblastic blood flow persisted. In contrast to the ultrasonographic findings, marked reduction of uteroplacental neovascularization at the CSP site with regression of the draining ovarian vein was evident on 3D-CTA. The gestational products were thereafter successfully resected by hysteroscopic surgery without hemorrhagic complications. Fifty-seven days after the initial MTX administration, serum β-hCG reached a normal level. Conclusion: This case emphasizes that, when selecting the method of intervention, 3D-CTA is potentially useful for evaluating uteroplacental neovascularization in a hemodynamically stable CSP.